Pengaruh media sosial terhadap pendidikan siswa di era digital dengan presepektif teori belajar kostruktivisme - Subakir, Nizarudin Zahid (Maliki Interdisciplinary Journal, 2025)
Overseas in the digital age, social media has become an important part of students’ lives, influencing their learning patterns and interactions with information. Throught the prespective of constructivism theory, this study aims to understand the role of social media insupporting and inhibiting students’ learning processes. Constructivism theory focuses onlearning as an active process in which students construct knowledge throught interactions with the environtment and their prior understanding. In this context, social media provides a platform for sharing knowledge, discussing and collaborating, all of which ecourage independent and interactive knowledge construction, but the use of social media also presents challenges, such a focus disturbanses and the risk of spreading inaccurate information. The results of this study indicate that, whith proper management and guidance, social media canbe a tool that supports the constructivist learning process effectively for students.